Bilangan Kromatik Lokasi pada Graf Hasil Amalgamasi Sisi dari Graf Bintang dan Graf Lengkap - Hartiansyah, Fiqih; Darmaji, Darmaji (Zeta - Math Journal, 2023)
The locating coloring of graph extends the vertex coloring dan partition dimension of graph. The minimum number of locating coloring of graph G is called the locating chromatic number of graph G. In this paper will discuss the locating chromatic number of edge amalgamation graph of star graph with order m+1 and complete graph with order n. The method used to obtain the locating chromatic number of graph is to determine the upper dan lower bound. The results obtained are that the locating chromatic number of edge amalgamation graph of star graph with order m+1 and complete graph with order n is for and .